Human trafficking, human security and the Balkans (The security continuum global politics in the modern age, 2007)
Human trafficking and the Balkans / H. Richard Friman and Simon Reich -- Trafficking exchanges and economic responses : reflections from Bosnia and Herzegovina and Serbia / Lynellyn D. Long -- Combating trafficking : international efforts and their ramifications / Julie Mertus and Andrea Bertone -- Transnational responses to human trafficking : the politics of anti-trafficking in the Balkans / Nicole Lindstrom -- Peacekeeping and rule breaking : United Nations anti-trafficking policy in Bosnia and Herzegovina / Martina E. Vandenberg -- Human trafficking and democratic transition in Albania / Vasilika Hysi -- Policy responses to human trafficking in the Balkans / Gabriela Konevska -- Human trafficking and human security / H. Richard Friman and Simon Reich